HUBUNGAN TINGKAT PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN MOTIVASI BERHENTI MEROKOK KEPADA KEPALA KELUARGA - Agnesia Indras Ayu Pangesti; Sondang Ratnauli Sianturi (Jurnal Penelitian Keperawatan Medik, 2026)
Introduction: Smoking is a cause of health problems throughout the world. The age group of 25-44 years is an adult age group, and already has a job, a steady income, married and has the ability to buy and consume cigarettes. Heads of families who smoke are restricted in their smoking space, because they want to protect their children or wives. However, quitting smoking is difficult so it requires strong motivation. Purpose: to identify the relationship between the level of knowledge and family support of the motivation to quit smoking among the heads of households. Method: The method used was correlation analytical research with a cross-sectional approach carried out on 116 samples of heads of families who were active smokers. The research was conducted June – July 2024. Result: The results obtained were that 48.3% of respondents were early adults, 95.7% were actively working, 77.6% had a high school education, 76.7% had a good level of knowledge, 45.7% had a good level of family support, 56.9% have a high level of motivation to quit smoking. The results of Kendall's tau B analysis showed that there was a relationship between the level of knowledge and motivation to stop smoking with a p-value of 0.020 and the level of family support and motivation to quit smoking with a p-value <0.001. Conclusion: It is intended that there will be health education promotions with posters or seminars about smoking to increase motivation to quit smoking.